IMMUNOMODULATING EFFECTS OF RASAYANA DRUGS IN DIABETICS – A CLINICAL STUDY - Arora, Deepa (Medknow Publications & Media Pvt Ltd, 2002)
Immune system plays an important role in pathogenesis of diabetes (DM). Besides hypoglycaemics, rasayanas are indicated in the management of DM. In several studies the immunomodulatroy potentials of rasayanas have been proved. A clinical trial of three rasayana drugs, Asparagus recemosus (AR). Bacopa monnieri (BM) and Centella asiatica (CA) was carried out in diabetics. In this study, diabetics were found to have significantly lower levels of serum IgG, increased serum IgA and comparable levels of IgM. All drugs reverted levels of serum IgG levels in diabetics, however, statistical significance was attained only with AR. Further the increased IgA levels were brought back towards normal. These drugs also increased serum protein levels.